Mycoflora of wheat straw : effects of environmental factors on spoilage and straw quality - Willcock, Joanne (Cranfield University, 1998)
The effect on the mycoflora, succession and deterioration of straw quality over a range of environmental conditions, including 0.75 to 0.98 water activity (aw), 10- 30°C and pH 4.4-6.4 were investigated. Isolation and colonisation of natural mycoflora and individual fungal species were significantly influenced by temperature x aw x pH interactions (P <0.05). Generally, the least growth occurring at 0.75 aw and 10°C, and the maximum at 0.98 aw and 30°C. Small scale respiratory apparatus was modified to measure respiration of the natural mycoflora and five individual species (Alternaria alternata, Cladosporium cladosporioides, Eurotium amstelodami, Fusariwn culmorum and Pénicillium aurantiogriseum) on wheat straw for the first time. Respiratory activity significantly increased with increasing temperature and aw (P <0.05). At the highest temperature (30°C) there was almost a linear increase, whereas at the lowest temperature (10°C), a lag time occurred prior to increased respiratory activity. Maximum dry matter losses (DML) were found to be 3.40 % at 30°C and 0.98 aw. Dry matter losses were found to change with storage period, and temperature x aw interactions. Significant loss of the carbohydrate components (P <0.05), assuming no loss of true lignin, was observed at 20°C when the apparent lignin content rose with increasing aw and, once 0.90 aw had been reached, remained at 140 % of the starting value. Of three biocides (Adesol 20, Busan 881 and Lastil 40), Lastil 40 was found to be most effective in vitro and on straw of significantly reducing fungal populations. Field trials with biocides and Nutri-Shield® at different storage moisture contents demonstrated that wads of straw on the surface of the top bales of the stack at 15 and 23 % moisture content provided the most effective storage treatment and significantly conserved the straw quality (P <0.05). All of the treatments, except wads of straw in nets, had increased apparent lignin contents, which showed that degradation had occurred.